2004
DOI: 10.1073/pnas.0308565100
|View full text |Cite
|
Sign up to set email alerts
|

Agonist-induced Ca 2+ entry determined by inositol 1,4,5-trisphosphate recognition

Abstract: It has been considered that Ca 2؉ release is the causal trigger for Ca 2؉ entry after receptor activation. In DT40 B cells devoid of inositol 1,4,5-trisphosphate receptors (IP3R), the lack of Ca 2؉ entry in response to receptor activation is attributed to the absence of Ca 2؉ release. We reveal in this article that IP 3 R recognition of IP 3 determines agonist-induced Ca 2؉ entry (ACE), independent of its Ca 2؉ release activity. In DT40 IP3R ؊/؊ cells, endogenous ACE can be rescued with type 1 IP3R mutants (bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 63 publications
(65 citation statements)
references
References 30 publications
3
62
0
Order By: Relevance
“…4B, red trace) almost doubles Ca 2ϩ release in response to purinergic receptor activation by UTP, although exerting no effect on subsequent agonist-induced Ca 2ϩ entry. These findings fit with previous evidence that IP 3 R-mediated Ca 2ϩ release and Ca 2ϩ entry are distinct processes (13). Depletion of RACK1 by siRNA profoundly reduces IP 3 R Ca 2ϩ release in response to UTP with no effect on subsequent Ca 2ϩ entry (Fig.…”
Section: Rack1 Binds Ip3rsupporting
confidence: 81%
See 1 more Smart Citation
“…4B, red trace) almost doubles Ca 2ϩ release in response to purinergic receptor activation by UTP, although exerting no effect on subsequent agonist-induced Ca 2ϩ entry. These findings fit with previous evidence that IP 3 R-mediated Ca 2ϩ release and Ca 2ϩ entry are distinct processes (13). Depletion of RACK1 by siRNA profoundly reduces IP 3 R Ca 2ϩ release in response to UTP with no effect on subsequent Ca 2ϩ entry (Fig.…”
Section: Rack1 Binds Ip3rsupporting
confidence: 81%
“…In all of these experiments, we observe no effects of RACK1 overexpression or its deletion on Ca 2ϩ entry (data not shown). This independent regulation of Ca 2ϩ entry and release accords with other studies (8,13).…”
Section: Rack1 Binds Ip3rsupporting
confidence: 77%
“…We found that a mutant DT40 cell line lacking all three IP 3 receptor isoforms (IP 3 R Ϫ/Ϫ cells) also lacked this PLC-dependent nonstore-operated cation entry, a finding more recently confirmed by others (9,10). If DT40 cells express only a single non-storeoperated entry involving TRPC7, one would expect that the lack of non-store-operated cation entry in IP 3 R Ϫ/Ϫ cells would be accompanied by absence of the OAG-regulated cation entry pathway.…”
Section: Trpc7supporting
confidence: 68%
“…Rather, in the avian B-cell line, TRPC7 appears to function as a PLC-regulated, DAG-activated non-selective cation channel. However, previous studies from this laboratory (8) and others (9,10) showed that in DT40 cells non-store-operated Ca 2ϩ , receptor-regulated cation entry depends in some manner on inositol trisphosphate (IP 3 ) receptors, but the precise role of IP 3 receptors (IP 3 R) in this pathway has not been defined. Because a Ca 2ϩ -impermeable mutant of the IP 3 R failed to rescue Ca 2ϩ entry in IP 3 R knock-out cells, we speculated that this entry might involve plasma membrane IP 3 R (8).…”
Section: Canonical Transient Receptor Potential (Trpc)mentioning
confidence: 98%
“…It has been shown that agoniststimulated intracellular Ca 2+ transients are biphasic, with the initial, transient rise in Ca 2+ representing sarcoplasmic Ca 2+ release (1)(2)(3)(4), and the later sustained Ca 2+ response representing predominantly Ca 2+ influx (1)(2)(3)(4). One of the mechanisms of extracellular Ca 2+ influx is the so-called store-operated Ca 2+ entry (2)(3)(4)(5). The store-operated Ca 2+ entry (also called capacitative Ca 2+ entry) appears to be mediated by a large family of channels called the transient receptor potential ion channels (TRPC; [2][3][4][5].…”
Section: Introductionmentioning
confidence: 99%